2016
DOI: 10.1371/journal.pone.0145958
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aldosterone Antagonists on Sudden Cardiac Death Prevention in Heart Failure and Post-Myocardial Infarction Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background and ObjectivesSudden cardiac death (SCD) is a severe burden of modern medicine. Aldosterone antagonist is publicized as effective in reducing mortality in patients with heart failure (HF) or post myocardial infarction (MI). Our study aimed to assess the efficacy of AAs on mortality including SCD, hospitalization admission and several common adverse effects.MethodsWe searched Embase, PubMed, Web of Science, Cochrane library and clinicaltrial.gov for randomized controlled trials (RCTs) assigning AAs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“… 59 Mineralocorticoid receptor antagonists or antialdosterone drugs have been reported effective in HFrEF by reducing SCD and all-cause mortality. 21 22 54 60 Our summary of the findings and the consistency of the results support this claim with a high quality of evidence. Only one retrieved meta-analysis 23 supported the effectiveness of combined ARB/neprilysin inhibitor.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“… 59 Mineralocorticoid receptor antagonists or antialdosterone drugs have been reported effective in HFrEF by reducing SCD and all-cause mortality. 21 22 54 60 Our summary of the findings and the consistency of the results support this claim with a high quality of evidence. Only one retrieved meta-analysis 23 supported the effectiveness of combined ARB/neprilysin inhibitor.…”
Section: Discussionsupporting
confidence: 71%
“…Published studies about mineralocorticoid receptor antagonists (antimineralocorticoids) or (so-called) antialdosterones appeared effective in SCD and all-cause mortality prevention. 21 22 54 However, in a recent systematic review, 21 adverse effects (hyperkalaemia, degradation of renal function and gynaecomastia) were significantly higher in the antialdosterone-treated group compared with placebo. The quality of the evidence was rated high with relative effect for SCD (RR 0.81, 95% CI (0.67 to 0.98)) and all-cause mortality (RR 0.81, 95% CI (0.74 to 0.88)) ( table 2 ).…”
Section: Effective Interventionsmentioning
confidence: 96%
“…The value of I 2 between 0 and 25% represents insignificant heterogeneity, 26 and 50% as low heterogeneity, 51 and 75% as moderate heterogeneity, and more than 75% as high heterogeneity. [ 24 ] Subgroup analysis was performed to explore the sources of heterogeneity. Evidence of publication bias was assessed with funnel plots by Egger's and Begg's linear regression.…”
Section: Methodsmentioning
confidence: 99%
“…Direct deleterious effects of aldosterone and mineralocorticoid receptor (MR) activation occur in both the heart and kidneys [ 2 ]. MR blockade prevents some of these detrimental effects and markedly improves morbidity and mortality of patients with moderate to severe heart failure as evidenced by large randomized controlled clinical multi-center trials [ 3 6 ]. De Boer and colleagues showed that MRA use markedly increased over the last 20 years among patients with diabetic kidney disease, who are at high risk for vascular complications [ 7 ].…”
Section: Introductionmentioning
confidence: 99%